THE MARINES RESOURCES: AN ALTERNATE TO THE AIDS TREATMENT - Lather, Amit; Kumar, Harsh; Kumar, Sunil; Hooda, Tanuj; Khatri, RC (Asian Journal of Pharmaceutical Research and Development, 2013)
Several useful drugs have been recently developed for the treatment of AIDS and the prevention of its onset in carriers of its causative virus i.e. human immune deficiency virus (HIV). However the rapid appearance of HIV strains resistant to the currently available drugs suggests that the effective treatment of this disease require innovative drugs having diverse mechanisms of anti-HIV activity. Also many of these drugs have severe side effects like inhibition of haemopoetic system making it essential to develop new effective drugs with less toxicity. The current article deals with latest available marine raw resources for the treatment of AIDS and also provides as lead to the scientist for synthesis of new anti HIV drugs.